Key Performance Metrics for Green Warehousing in Manufacturing Supply Chains: A Review - Meliana, Dita; Hasibuan, Sawarni (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2025)
This research highlights the significance of adopting eco-friendly methods in storage, which is a vital part of the manufacturing supply chain. Although green warehousing is still in its early stages, and there is less literature and empirical data on the subject, its potential for sustainable growth is enormous and requires additional exploration. The study's objective is to identify areas in research that have not been adequately addressed and to establish key performance indicators (KPIs) relevant to green warehousing. This will be achieved by a thorough invesstigation of existing literature. The research methodology employs well-regarded databases such as Publish or Perish, Proquest, and Google Scholar. It utilizes keywords such as "key performance indicators" and "green warehousing". A study of bibliographic data is performed using VOS Viewer to find patterns and concentration of research in this field. The results provide a range of KPIs for environmentally friendly warehousing, such as energy usage, waste management, efficiency in utilizing warehouse space, and monitoring of carbon emissions. The discussion emphasizes the importance of using eco-friendly warehousing practices to decrease greenhouse gas emissions and improve the efficiency of supply chains. The study suggests that researchers create practical case studies based on observation and participate in interdisciplinary research. For professionals in the industry, it recommends adopting quantifiable KPIs and allocating resources to develop environmentally friendly infrastructure.